2011
DOI: 10.1007/s10126-011-9419-y
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Bioreduction of 1-(4-Methoxyphenyl)ethanone by Whole Cells of Marine-Derived Fungi

Abstract: Nine strains of marine-derived fungi (Aspergillus sydowii Ce15, A. sydowii Ce19, Aspergillus sclerotiorum CBMAI 849, Bionectria sp. Ce5, Beauveria felina CBMAI 738, Cladosporium cladosporioides CBMAI 857, Mucor racemosus CBMAI 847, Penicillium citrinum CBMAI 1186, and Penicillium miczynskii Gc5) were screened, catalyzing the asymmetric bioreduction of 1-(4-methoxyphenyl)ethanone 1 to its corresponding 1-(4-methoxyphenyl)ethanol 2. A. sydowii Ce15 and Bionectria sp. Ce5 produced the enantiopure (R)-alcohol 2 (>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Whole-cell based biocatalytic reduction has attracted great attention due to the unique advantages such as mild reaction conditions, environmental friendliness, regeneration of cofactors in situ, easy production and relatively low price; this method has therefore attracted great attention and been extensively investigated in recent years (Rodrigues et al 2004s;Schmid et al 2001;Wohlgemuth et al 2010). To date, there is a number of works on enzymatic reduction of prochiral carbonyl compounds to produce chiral alcohols involving biocatalysts of terrestrial origin (Ni et al 2013;Rocha et al 2012), but little using marine organisms or their purified enzymes (Rocha et al 2015;Trincone 2010;Veberlen et al 2006). As far as we know, most of the previously reported terrestrial microorganisms have not been used for industrial preparation of chiral alcohols for their relatively low catalytic activity and stereoselectivity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whole-cell based biocatalytic reduction has attracted great attention due to the unique advantages such as mild reaction conditions, environmental friendliness, regeneration of cofactors in situ, easy production and relatively low price; this method has therefore attracted great attention and been extensively investigated in recent years (Rodrigues et al 2004s;Schmid et al 2001;Wohlgemuth et al 2010). To date, there is a number of works on enzymatic reduction of prochiral carbonyl compounds to produce chiral alcohols involving biocatalysts of terrestrial origin (Ni et al 2013;Rocha et al 2012), but little using marine organisms or their purified enzymes (Rocha et al 2015;Trincone 2010;Veberlen et al 2006). As far as we know, most of the previously reported terrestrial microorganisms have not been used for industrial preparation of chiral alcohols for their relatively low catalytic activity and stereoselectivity.…”
Section: Discussionmentioning
confidence: 99%
“…When Penicillium strains, including Penicillium citrinum GIM 3.458 (strain G), Penicillium citrinum GIM 3.251 (strain H), Penicillium citrinum GIM 3.100 (strain I), and Aspergillus strains including Aspergillus sclerotiorum AS 3.2578 (strain J), Aspergillus sydowii AS 3.7839 (strain K), Aspergillus sydowii AS 3.6412 (strain L), were tested for ketone reductase activity using eight aromatic ketones (1a-1d and 1g-1j) as testing substrates, no desired reduction products were obtained. This result is surprising, as the Porto group (Rocha et al 2010(Rocha et al , 2012(Rocha et al , 2015de Oliveira et al 2014;De Vitis et al 2015) reported that Aspergillus sclerotiorum CBMAI 849 and Penicillium citrinum CBMA 1186 (Brazilian marine filamentous fungus) catalyzed the biotransformation of α-bromoacetophenones to the corresponding alcohols with good yields and enantioselectivities. Comparison of the results obtained with the tested Chinese Penicillium and Aspergillus strains to those reported for Brazilian strains suggests that strains from different sources have different expression of (different) enzymes, such as ketone reductases.…”
Section: Distribution Of Ketone Reductases In Various Marine Fungimentioning
confidence: 99%
See 1 more Smart Citation
“…Novel and robust microorganisms with perfect catalytic activity and stereoselectivity in the fields of biocatalytic reduction are in great demand. Future success can be achieved from the exploitation of marine microorganisms’ enzymatic potential [ 11 , 12 , 13 , 14 , 15 , 16 ]. Marine microorganisms are thoroughly adapted to surviving and growing under extreme environments, resulting in their production of novel enzymes with optimal biochemical properties at harsh conditions (extreme temperature, pressure, pH, or organic solvent) [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whole-cell based biocatalytic reduction has attracted great attention and has been extensively investigated in recent years for the unique advantages such as outstanding enantioselectivity, mild reaction conditions, environmental friendliness and regeneration of cofactors in situ [6-8]. So far, yeasts, bacteria, fungi, and even plant tissues have been extensively researched as biocatalysts for bio-reduction processes [9,10], and many excellent biocatalytic reaction processes have been developed. However, most of these biocatalysts follow Prelog’s rule [11], and thus the ( S )-alcohols are usually obtained when the smaller substituent of the ketone has the lower CIP priority.…”
Section: Introductionmentioning
confidence: 99%